Factors associated with feeding practices among Brazilian children aged 12 to 23 months old - Rebouças,Adriana Gama (2020)
Abstract Objectives: a quantitative analytical cross-sectional study aimed to identify demographic characteristics to access health services and housing conditions in relation to inadequate feeding practices among Brazilian children from 12 to 23 months of age. Methods: the analysis of the feeding practices (consumption of recommended food groups) of 2541 Brazilian children (aged 12-23 months old) was performed using data from the Pesquisa Nacional de Saúde 2013 (National Health Survey). Descriptive and multivariate statistics used the Decision Tree Analysis based on CHAID (Chi-squared Automatic Interaction Detector) algorithm, as well as hierarchically adjusted Poisson regression analyses were performed. The variables were entered in a hierarchical model at distal (demographic), intermediate (access to health) and proximal (housing conditions) levels. Results: the results showed a high prevalence of sugar consumption (85.5%; CI95%=83.7-87.2) and highlighted inadequate feeding practices among non-white children (p=0.001), resident in the North (p<0.001) and Northeast (p=0.010) of Brazil and in towns in the countryside (p<0.001) presented feeding practices that were not recommended for consumption in the food groups. Conclusions: non-white children, who lived in the North and Northeast regions of Brazil and in the countryside, which are known to be more socioeconomically vulnerable, were more likely to experience inadequate feeding practices.